OPTIMALISASI PENYUSUNAN MENU DIET PENDERITA STROKE DENGAN METODE GOAL PROGRAMMING - PRATIWI, NI MADE DINDA; GANDHIADI, G.K.; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 10 No 1 (2021), 2021)
Stroke is a disorder of brain nerve function caused by blockage of blood circulation to the brain. In preparing the diet for stroke, it is possible to deviate from the recommended nutritional value and total energy. This problem c ould be overcome by compiling a stroke diet menu using the Goal programming method. The purpose of this study is to determine whether the results of the portion of food obtained using the Goal programming method can meet the recommended energy and nutritional content targets, as well as knowing the percentage of total energy content produced per day from the preparation of the diet menu to the recommended total energy content. The calculations in this study using the help of LINGO software with the results that the diet menu by Goal programming method has met the recommended nutrients and energy from the standard stroke diet at Klungkung Hospital, and the percentage of energy fulfilled from the stroke IIB diet for three days shows a 100% result .